2022
DOI: 10.1177/10600280211069182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Continuous Inhaled Epoprostenol in the Treatment of Acute Respiratory Distress Syndrome, Including Patients With SARS-CoV-2 Infection

Abstract: Background Acute respiratory distress syndrome (ARDS) management is primarily supportive. Pulmonary vasodilators, such as inhaled epoprostenol (iEPO), have been shown to improve PaO2:FiO2 (PF) and are used as adjunctive therapy. Objective To identify the positive response rate and variables associated with response to iEPO in adults with ARDS. A positive response to iEPO was defined as a 10% improvement in PF within 6 hours. Methods This retrospective study included adults with ARDS treated with iEPO. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…It is unclear the exact reason for those with CARDS having an increased length of hospitalization but is most likely related to a multifactorial process involving the progression of the disease and the timing of a patient's illness. These data are consistent with recently published data that showed that those with CARDS had a 6.5-day longer stay than those with traditional ARDS [16]. Prior to making a formal recommendation on the usage of iEPO in CARDS, however, further randomized controlled trials are needed to assess the effects on patient-centered outcomes, including elucidating the reasons why patients with CARDS had a longer LOS as compared to those with ARDS.…”
Section: Discussionsupporting
confidence: 86%
“…It is unclear the exact reason for those with CARDS having an increased length of hospitalization but is most likely related to a multifactorial process involving the progression of the disease and the timing of a patient's illness. These data are consistent with recently published data that showed that those with CARDS had a 6.5-day longer stay than those with traditional ARDS [16]. Prior to making a formal recommendation on the usage of iEPO in CARDS, however, further randomized controlled trials are needed to assess the effects on patient-centered outcomes, including elucidating the reasons why patients with CARDS had a longer LOS as compared to those with ARDS.…”
Section: Discussionsupporting
confidence: 86%
“…62 This study also determined lower baseline P/F ratios and non-COVID-19 ARDS were significant predictors of positive response to iEPO. 62…”
Section: Inhaled Prostaglandinsmentioning
confidence: 68%
“…61 A multicenter retrospective study by Niss et al included patients with both COVID-19-associated ARDS and non-COVID-19 ARDS and saw a majority of patients having a positive response to iEPO, defined as greater than 10% increase in P/F ratio within 6 hours of administration. 62 This study also determined lower baseline P/F ratios and non-COVID-19 ARDS were significant predictors of positive response to iEPO. 62 Imtiaz et al performed a retrospective case series of patients with COVID-19-associated ARDS who received iEPO at an initial dose of 50 ng/kg/min.…”
Section: Clinical Efficacy In Covid-19-associated Ardsmentioning
confidence: 68%
“…Eventually, 18 studies were included in the 1-arm meta-analysis (13 single arm retrospective studies 18 30 and 5 case series 31 35 ) and three studies 13 , 14 , 36 in the 2-arm meta-analysis. Figure 1 shows the PRISMA flow chart that illustrates how the final studies were selected.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 782 studies underwent full-length review. Subsequently, we excluded 761 studies because of the following: 317 studies used interventions not involved in our study Eventually, 18 studies were included in the 1-arm metaanalysis (13 single arm retrospective studies [18][19][20][21][22][23][24][25][26][27][28][29][30] and 5 case series [31][32][33][34][35] ) and three studies 13,14,36 in the 2-arm meta-analysis. Figure 1 shows the PRISMA flow chart that illustrates how the final studies were selected.…”
Section: Study Selectionmentioning
confidence: 99%